ADMINISTRATIVE LAW ANALYSIS OF REGIONAL INVESTMENT INCENTIVE POLICIES AND ITS IMPACT ON REGIONAL ECONOMIC GROWTH - Firdaus Arifin (Jurnal Ilmiah Advokasi, 2024)
The implementation of investment incentive policies in regional areas often encounters obstacles due to legal uncertainty and inconsistencies in the application of administrative law, which negatively affect investment attractiveness and local economic growth. Effectively designed incentives, such as tax reductions, simplified licensing processes, and other supportive investment facilities, have been shown to increase investor interest in specific regions. This study aims to analyze the role of administrative law in supporting regional investment incentive policies and their impact on economic growth. Using a normative legal approach and qualitative analysis methods, the study reveals that consistent application of administrative law strengthens investor confidence in legal certainty. For example, regions that provide performance-based incentives and ensure legal protection for investments have demonstrated increased investment levels. Conversely, legal uncertainty and a lack of inter-agency coordination often lead to ineffective incentive policies, exacerbate economic disparities between regions, and weaken investment competitiveness. The findings highlight the need for reforms in the administrative legal framework, harmonization of incentive policies, and improved inter-agency coordination to ensure that investment incentive policies effectively promote inclusive and sustainable economic growth across Indonesia. Keywords: Administrative Law, Investment, Policy, Regional Economy